EVALUACIÓN DE NUEVOS CULTIVARES DE ARROZ (Oryza sativa L.) EN CONDICIONES DE BAJOS SUMINISTROS DE AGUA Y FERTILIZANTE EN LA PROVINCIA PINAR DEL RÍO - Elizabeth Cristo Valdés; María C. González Cepero; Noraida Pérez León (Cultivos Tropicales)
This work was conducted at “Los Palacios” Scientific-Technological Base Unit (STBU), belonging to the National Institute of Agricultural Sciences (INCA), located in “Los Palacios” municipality, Pinar del Río province, in order to study the behavior of eleven rice cultivars, derived from different breeding methods, compared with the commercial cultivar J-104, during the dry season of 2011 and rainy season of 2012, both under low water and fertilizer supply conditions. Water management consisted of establishing a layer 15 days after rice germination, suspending its entry 35 days after germination and putting it back at primordial change until after 50 % flowering. At harvest time, evaluations were performed to leaf number, final plant height, crop cycle, agricultural yield and its components, industrial yield as well as its resistance to lodging, shattering and the main pests. Jose LP-20 and Guillemar LP-19 cultivars achieved the best agricultural and industrial yields, resistance against Piriculariosis and black kernel.